Respiratory syndrome very similar to extrinsic allergic alveolitis due to Penicillium verrucosum in workers in a cheese factory - Guglielminetti, Maria; Valoti, Elio; Cassini, Pamela; Taino, Giuseppe; Caretta, Giuseppe (Mycopathologia (1975), 2001)
A respiratory syndrome very similar to extrinsic allergic alveolitis due to Penicillium verrucosum was recognized in 4 workers employed in a Gorgonzola cheese factory. A mycogen allergy to P. verrucosum, used as starter in the production, was demonstrated by positive sputum culture and detection of specific antibodies in the blood. Intense and prolonged exposure to inhalation of fungal spores could have lead to the development of this allergic response. The fact that 2 of the subjects are siblings seems to indicate host susceptibility or immunological constitution in the pathogenesis of the respiratory allergy.